Pengembangan Instrumen Assesmen Literasi Sains Berbasis Kontekstual pada Materi Koloid - Latifa Salsabilah, Ince Husnul; Husain, Halimah; Sudding, Sudding (Program Pasca Sarjana UNM, 2024)
This research is a development research (Research and Development) with the objectives: (1) to assess the quality of the instrument in terms of content validity and empirical validity, (2) to determine the reliability of the developed instrument, and (3) to assess the practicality of the developed instrument. The product developed is a contextual science literacy assessment instrument on the topic of colloids. The developed contextual science literacy instrument is in the form of multiple-choice questions. The research was conducted using the 4D development model, which includes the stages of define, design, develop, and disseminate. The results of rational validation by two expert validators yielded 15 valid test items with an Aiken's index ≥ 0.75. The instrument was tested on 34 students from class XII MIPA 3 of SMAN 1 Gowa. The results of empirical validation using the point biserial formula at α=0.339 yielded 14 valid test items. The results of the reliability test using KR-20 showed that the instrument was categorized as reliable with a value of 0.831. The analysis of the item discrimination power showed that there were 2 very good items, 6 good items, 4 fair items, and 3 poor items. The distribution of the item difficulty level was 47% difficult items, 40% medium items, and 2% easy items. The practicality of the contextual science literacy assessment instrument on the topic of colloids was categorized as practical based on the positive results of the student questionnaire (85%) and the teacher questionnaire (95%).